Criminological characteristics of the personality of extremist (Journal of actual problems of jurisprudence, 2018)
In this article the author considers very complex, many sided and many aspect of the problem as the identity of the extremist. An attempt was made to give a General description of the identity of the person extremist, its socio-demographic and psychological entity, as well as disclosure of the reasons contributing to commit extreme action. We study the complexity of the psychological mechanism of individual persons extremist, the causes of the needs of the individual in expression. On the basis of statistical data factors and social status of the offender contributed to the Commission of this crime.Key words: the identity of the offender, socio-demographic characteristics. representatives of non-traditional religions. mental disorder. religious science.